2020
DOI: 10.1186/s13613-020-0637-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of deprivation on initial severity and prognosis of patients admitted to the ICU: the prospective, multicentre, observational IVOIRE cohort study

Abstract: Background: The influence of socioeconomic status on patient outcomes is unclear. We assessed the impact of socioeconomic deprivation on severity of illness at intensive care unit (ICU) admission, and on the risk of death at 3 months after ICU admission. Methods: The IVOIRE study was a prospective, observational, multicentre cohort study in the ICU of 8 participating hospitals in France, including patients aged ≥ 18 years admitted to the ICU and receiving at least one life support therapy for organ failure. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 52 publications
3
24
0
Order By: Relevance
“…The risk of adverse health events, ICU admission and death are thought to be higher in people living in more deprived areas and this has been indicated in England and more recently in our study in Wales [3,14]. Interestingly international comparisons do not support this, notably in France multiple studies have shown no adverse association with low socioeconomic status and initial severity of illness on ICU admission or long-term outcome [15][16]. Currently, there is no definitive data on this subject in relation to COVID-19 disease.…”
Section: Discussionsupporting
confidence: 51%
“…The risk of adverse health events, ICU admission and death are thought to be higher in people living in more deprived areas and this has been indicated in England and more recently in our study in Wales [3,14]. Interestingly international comparisons do not support this, notably in France multiple studies have shown no adverse association with low socioeconomic status and initial severity of illness on ICU admission or long-term outcome [15][16]. Currently, there is no definitive data on this subject in relation to COVID-19 disease.…”
Section: Discussionsupporting
confidence: 51%
“…Socioeconomic advantage and disadvantage did not contribute to mortality in the present study, consistent with previous studies. 31,32 However, increasing remoteness was associated with decreased mortality risk, a finding that has been reported previously in non-CKD5Dspecific studies. 33 There are several potential explanations for this finding.…”
Section: Discussionsupporting
confidence: 59%
“…The risk of adverse health events, ICU admission and death are thought to be higher in people living in more deprived areas and this has been indicated in England and more recently in our study in Wales ( 3 , 20 ). Interestingly international comparisons do not support this, notably in France multiple studies have shown no adverse association with low socioeconomic status and initial severity of illness on ICU admission or long-term outcome ( 21 , 22 ). Currently, there is no definitive data on this subject in relation to COVID-19 disease.…”
Section: Discussionmentioning
confidence: 98%